The London Lock Charities in the middle to late Victorian Period: poor reform beyond venereal disease - Romero-Ruiz, María Isabel (My University, 2015)
The London Lock Hospital was founded in the middle of the seventeenth century to cure venereal disease both in men and women, following the trend of specialized hospitals that proliferated in the period. A few decades later, the London Lock Asylum was erected by public subscription to seclude fallen women released from hospital who showed an inclination at reform. However, by the second half of the nineteenth century, another philanthropic activity was added to that of the Hospital and Asylum, which consisted in the development of two new branches of the Institution: the Missionary one and the Educational one. Following the pattern of Lady Visitors who devoted their time to the religious instruction of inmates in institutions and working-class homes of the 1860s to the 1890s, City Missionaries proliferated and the London Lock became involved in this movement and was known as the Dean Street Mission. The Mission Woman did rescue-work with female out-patients but also visited them in their homes and places of accommodation. Also, through the London Lock Chapel, a number of organizations were established to help the poor of the district with food, clothes and money matters such as the Friendly Visiting Society, the London City Mission (Westbourne Green District), the Provident Society, the Westbourne Penny Provident Bank, the Soup Kitchen and the Dorcas Society. As far as education and religious instruction were concerned, the Westbourne Schools, St. John’s Servants’ School, Bible classes, and Sunday and Night Schools were run to provide children, men and women with some basic knowledge or to train them in working-class professions. Finally, leisure activities were organized together with the educational ones, and the Mission House and the Young Men’s Society provided people in the area with instruction in moral habits and decent entertainment. Therefore, the aim of this paper is to prove how the London Lock became involved as an Institution in the process of indoctrinating and educating the poor and the former inmates of the Hospital and Asylum as well as in the philanthropic and missionary work which characterized the Social Purity Movement of the latter part of the Victorian period. As happened with similar institutions of the time, the evangelical spirit and the middle-class values in relation to notions of morality and respectability impregnated all the activities aimed at the reformation of the working poor and the transformation of their identities. The information in this paper is based on the research conducted on the archives kept at the Royal College of Surgeons of England in London, and informed by a postmodern and discourse theory approach to the history of medicine.
Keywords: Enfermedades venéreas - Tratamiento - S. XIX; Gran Bretaña - Situación social - Historia -1837-1901; London Lock; Victorian period; Reform; Venereal disease; Charities